Mekanisme Pelarian: Alasan Orang Dewasa Menonton Streaming Video Game - Syahara Haniq Aini; Suci Nugraha (UNISBA Press, 2024)
Abstract. Individuals can divert themselves from the burden and tension of monotonous routines in various ways, for example by watching others play games through live streaming, which is currently a digital media as entertainment. This research presents an exploration of how audience interaction behavior in video game live streaming arises as a need for individual escapism. Two models of escapism proposed by Stenseng (2009), namely escapism as self-suppression and self-expansion are associated with interactions in live streaming video games to determine the relationship between the two. This study uses a correlational quantitative research design and uses a questionnaire in data collection. The sampling technique used was convenience sampling and involved participants who actively consumed live streaming video games (n = 402). The research instrument used was a questionnaire developed based on the model of Stenseng et al. (2012) which has been adapted into Indonesian and the context of live streaming video games. The results showed that there was a significant positive correlation between the two dimensions of escapism and interaction behavior in video game live streaming. The findings provide an understanding of how individuals use digital media as an individual escape and uncover the psychological aspects behind the interactions that occur in live video game broadcasts and insights for the gaming industry especially the streamer community in broadcasting content as well as how to develop the community and create a more positive experience for the audience. Abstrak. Individu dapat mengalihkan diri dari beban dan ketegangan rutinitas yang monoton dengan berbagai cara misalnya dengan menonton orang lain bermain game melalui live streaming yang saat ini menjadi media digital sebagai hiburan. Penelitian ini memaparkan eksplorasi mengenai bagaimana perilaku interaksi penonton dalam siaran langsung video game yang muncul sebagai kebutuhan dari pelarian individu. Dua model pelarian yang diajukan oleh Stenseng (2009), yaitu pelarian sebagai self-suppression dan self-expansion dikaitkan dengan interaksi dalam siaran langsung video game untuk mengetahui adanya hubungan antara keduanya. Penelitian ini menggunakan desain penelitian kuantitatif korelasional dan menggunakan kuesioner dalam pengambilan data. Teknik sampling yang digunakan yaitu convenience sampling dan melibatkan partisipan yang aktif mengonsumsi video game live streaming (n = 402). Instrumen penelitian yang digunakan adalah kuesioner yang dikembangkan berdasarkan model Stenseng et al. (2012) yang telah diadaptasi ke dalam bahasa indonesia dan konteks video game live streaming. Hasil penelitian menunjukkan bahwa terdapat korelasi positif yang signifikan antara kedua dimensi pelarian dengan perilaku interaksi dalam siaran langsung video game. Temuan ini memberikan pemahaman tentang bagaimana individu menggunakan media digital sebagai pelarian individu dan mengungkap aspek psikologis dibalik interaksi yang terjadi dalam siaran langsung video game dan wawasan bagi industri game terutama komunitas streamer dalam menyiarkan konten juga bagaimana mengembangkan komunitas serta menciptakan pengalaman yang lebih positif bagi penonton.